Sulfhydryl Functionalized Magnetic Chitosan as an Efficient Adsorbent for High-Performance Removal of Cd(II) from Water: Adsorption Isotherms, Kinetic, and Reusability Studies - Jari S. Algethami; Ayoub Abdullah Alqadami; Saad Melhi; Mohsen A. M. Alhamami; Ahmed M. Fallatah; Moustafa A. Rizk (Adsorption Science & Technology)
In this study, dimercaptosuccinic acid-functionalized magnetic chitosan (Fe3O4@CS@DMSA) was synthesized via in situ coprecipitation process and amidation reaction, aiming to eliminate cadmium (Cd(II)) ions from an aqueous environment. The structure, morphology, and particle size of the Fe3O4@CS@DMSA adsorbent were investigated using FTIR, TEM, EDX, TGA, zeta potential, and XRD techniques, and the obtained results approved the successful synthesis of the Fe3O4@CS@DMSA nanocomposite. The influence of external adsorption conditions such as pH solution, adsorbent mass, initial Cd(II) concentration, temperature, and contact time on the adsorption process was successfully achieved. Accordingly, pH: 7.6, contact time: 210 min, and adsorbent mass:10 mg were found to be the optimal conditions for best removal. The adsorption was analyzed using nonlinear isotherm and kinetic models. The outcomes revealed that the adsorption process obeyed the Langmuir and the pseudo-first-order models. The maximum adsorption capacity of Fe3O4@CS@DMSA toward Cd(II) ion was 314.12 mg/g. The adsorption mechanism of Cd(II) on Fe3O4@CS@DMSA nanocomposite is the electrostatic interaction. The reusability test of Fe3O4@CS@DMSA nanocomposite exhibited that the adsorption efficiency was 72% after the 5th cycle. Finally, this research indicates that the Fe3O4@CS@DMSA exhibited excellent characteristics such as high adsorption capacity, effective adsorption-desorption results, and easy magnetic separation and thus could be an effective adsorbent for removing Cd(II) ions from aqueous solutions.